Effects of an isostretching training protocol to increase the musculoarticular flexibility and other physiological aspetcs on the quality of life - Faria, Flávia Amélia Costa; Reis, Lara Rodrigues; Neiva, Cassiano Merussi [UNESP] (My University, 2010)
Purpose: To apply the technique of Isostretching in a group of people over age 50 years and compare the flexibility of the posterior muscular chain before and after treatment, observing whether there was improvement in quality of life after the end of the sessions. Method: Eleven healthy and sedentary people from 51 to 74 years old participated in the study, which was conducted in Brazil. To evaluate the flexibility we applied the SF-36 questionnaire and test flexion of the spine before and after the study. Eight domains were accessed with the scores ranging form zero to one hundred. Results And Discussion:The technique was effective to gain flexibility of the posterior muscle group, which results in better quality of life for the participants. The results show that the domains related to physical health obtained the highest scores (“functional capacity”, “limitation in physical aspects” and “pain”). These aspects are strongly emphasised in a physical therapy treatment.

Obiectivul principal al acestui studiu a fost să se aplice tehnica Isostretching într-un grup de persoane cu varsta peste 50 de ani şi compara flexibilitatea lanŃului musculare posterioare înainte şi după tratament, cu respectarea dacă a existat în îmbunătăŃirea calităŃii vieŃii după încheierea sesiunilor . Unsprezece persoane sănătoase şi sedentari 51 la 74 de ani au participat la studiu, vrajitoare a fost făcut în Brazilia. Pentru a evalua flexibilitate am aplicat chestionarul SF-36 şi flexie a coloanei vertebrale de testare înainte şi după studiu. Opt domenii au fost accesate cu scoruri variind formularul de zero la sută. Tehnica a fost eficient pentru a obŃine flexibilitatea grupa musculara posterioara, rezultate în vrăjitoare bună calitate a vieŃii pentru participanti. Rezultatele arată că domeniile legate de sănătatea fizică a obŃinut cele mai mari note ("capacitatea funcŃională," limitarea în aspectele fizice "şi" durere"). Acest aspecte sunt puternic subliniat într-un tratament terapie fizică.
Keywords: Isostretching; Flexibility; SF-36 questionnaire; Posterior muscle group; Isostretching; Flexibilitate; Chestionarul SF-36; Grupa de muschi posterioară